1975
DOI: 10.1021/bi00692a029
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced self-association of human chorionic gonadotropin. Positive cooperativity in the binding of 8-anilino-1-naphthalenesulfonate

Abstract: Human chorionic gonadotropin (hCG) self-associates to form higher molecular weight species in the presence of the fluorescence probe 8-anilino-1-naphthalenesulfonate (ANS). Sedimentation equilibrium and fluorescence titration data have been analyzed in terms of a monomer-dimer-tetramer model in which the various oligomers have different affinities and/or capacities for the ligand. The results indicate that the ligand affinities are in the order tetramer greater than dimer greater than monomer whereas the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The concentration of ANS required for half-maximal saturation was ~20 µ . However, subsequent studies of this interaction revealed that hCG self-associates to form dimers ( 2ß ) and tetramers (onfif) in the presence of ANS and that enhancement of ANS fluorescence was due to binding by these oligomers (Ingham et al, 1975). This finding compelled us to confirm that ANS fluorescence is enhanced only by the native intact form of the hormone and that the presence of ANS in the recombination mixture does not influence the rate of that reaction.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The concentration of ANS required for half-maximal saturation was ~20 µ . However, subsequent studies of this interaction revealed that hCG self-associates to form dimers ( 2ß ) and tetramers (onfif) in the presence of ANS and that enhancement of ANS fluorescence was due to binding by these oligomers (Ingham et al, 1975). This finding compelled us to confirm that ANS fluorescence is enhanced only by the native intact form of the hormone and that the presence of ANS in the recombination mixture does not influence the rate of that reaction.…”
Section: Resultsmentioning
confidence: 92%
“…This conclusion is further supported by the agreement between the rates of recombination as measured by the two assays (Figure 2). The fact that hCG self-associates to form dimers (o^/Sa) and tetramers (a^f) in the presence of ANS (Ingham et al, 1975) was utilized in the present report as an aid in the purification of commercial hCG by gel chromatography (see Methods). A similar approach might be useful for relieving subunit preparations of contamination by intact hormone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some diminution is observed in the recombination product α-native-+ des-( 143-145 )-|3-subunit. Ans induces aggregation of choriogonadotropint 25 '. This was used to investigate whether the reduced Ans-choriogonadotropin fluorescence of recombination products containing a modified a-and a native (3-subunit might be caused by a loss of binding ability for Ans by a portion of the recombined hormone.…”
Section: Complex Formation Between Digested Choriogonadotropin and Ansmentioning
confidence: 99%